2020
DOI: 10.37897/rjn.2020.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Azithromycin nanoparticles: Cyclic voltammetric study in human blood serum samples at electrochemical analysis

Abstract: In a new study to identify one of the anti-inflammatory, such as azithromycin and its effects on the composition of blood using one of the methods of electrochemical analysis and converted to nanoparticles using cyclic voltammetry. It was found that azithromycin nanoparticles (AZNPs) has oxidation-reduction current peaks in blood medium at 1 and 0.75 V respectively, these peaks were affected by different pH, the anodic peak was disappeared in alkaline blood medium, while the redox peaks enhanced in acidic bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7 and 8, with the Randel equation, the values of diffusion coefficient are calculated below: Df (Ipa1) = 3.06x10 -6 Df (Ipa2) = 5.43x10 -6 Df (Ipc) =1.96x10 -6 The modification of GCE with nanoparticles such as fMWCNT, which has a new phenomenon of the electrochemical conductivity in the cyclic voltammetry by enhancement the redox current that leading to the close diffusion coefficient values as in the above values. These results were indicated that the oxidation-reduction process of the paracetamol compound is a reversible reaction on the modified electrode (fMWCNT/GCE) [18].…”
Section: E Determination Of Diffusion Coefficientmentioning
confidence: 85%
“…7 and 8, with the Randel equation, the values of diffusion coefficient are calculated below: Df (Ipa1) = 3.06x10 -6 Df (Ipa2) = 5.43x10 -6 Df (Ipc) =1.96x10 -6 The modification of GCE with nanoparticles such as fMWCNT, which has a new phenomenon of the electrochemical conductivity in the cyclic voltammetry by enhancement the redox current that leading to the close diffusion coefficient values as in the above values. These results were indicated that the oxidation-reduction process of the paracetamol compound is a reversible reaction on the modified electrode (fMWCNT/GCE) [18].…”
Section: E Determination Of Diffusion Coefficientmentioning
confidence: 85%
“…[4] Many adults and children use it for respiratory tract infections, skin and soft tissue infections, moderate otitis media, sinusitis, pharyngitis, cystic fibrosis, severe bronchitis, GIT infections, tonsil infections, and as an anti- inflammatory in patients with chronic obstructive pulmonary disease [5,6]. And is among the antibiotics with the top sales worldwide [7].There were different published articles for the analysis of AZ in different pharmaceutical and biological forms various analysis techniques are used in these published articles such as spectrophotometry [8][9][10] ,HPLC [11,12], RP-HPLC [13][14][15], glassy carbon [16], cyclic voltammetry [17] flow injection-Amperometric [18] and UV Radiation [19].…”
Section: Introductionmentioning
confidence: 99%
“…This study investigates the effect of drugs on rabbit blood components using cyclic voltammetry [1][2][3][4][5][6]. An adjuvant is a component that enhances the immune response to the vaccine.…”
Section: Introductionmentioning
confidence: 99%